2021
DOI: 10.14742/ajet.6623
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smartphone-based collaborative vlog projects on EFL learners’ speaking performance and learning engagement

Abstract: This study examined how smartphone-based collaborative video projects influenced English as a Foreign Language (EFL) learners’ speaking performance and learning engagement using blended learning in China. The collaborative video projects helped students engage in two smartphone-based video filming tasks to combine language learning with real-life experiences simultaneously. A total of 65 college students used smartphones to participate in 3-minute collaborative video tasks that were related to the learning con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 45 publications
1
44
0
Order By: Relevance
“…This variety showed creativity from the students in making their video presentations. Huang (2021) found that all 65 of the students he interviewed had a positive perception of the video projects conducted in the class. Students' reasons for these sentiments included digital media production skills, communication with each other, and multiple proficiencies.…”
Section: Building Efl Skills Through Video Presentationsmentioning
confidence: 97%
See 4 more Smart Citations
“…This variety showed creativity from the students in making their video presentations. Huang (2021) found that all 65 of the students he interviewed had a positive perception of the video projects conducted in the class. Students' reasons for these sentiments included digital media production skills, communication with each other, and multiple proficiencies.…”
Section: Building Efl Skills Through Video Presentationsmentioning
confidence: 97%
“…Students reported that their English level had improved through video presentations (Cowie & Sakui, 2018;El-Garawany, 2017;Kulsiri, 2018;Naqvi & Al Mahrooqi, 2016;Santhi, Suherdi, & Musthafa, 2019;Stanley & Zhang, 2018). Huang (2021) recorded statistically significant higher test scores from students after completing video tasks in the classroom. Mali (2018) attributed part of the language gains observed to the opportunity for students to "repetitive learning behaviors they did in completing the project" (p. 15).…”
Section: Building Efl Skills Through Video Presentationsmentioning
confidence: 99%
See 3 more Smart Citations